The Effects of Police Effort on Victims’ Fear of Crime - Abbott, Jessica (American journal of criminal justice, 2020)
In this study, we sought to assess whether increased police effort subsequent to an individual’s criminal victimization has a significant effect on violent crime victims’ fear of crime. Extant literature shows somewhat incongruent findings with regard to whether and in what way general police actions and effort (police presence in a community, increased interactions with members of a community) have an effect on fear in communities. To date, there has been a gap in the literature concerning fear of crime of crime victims, and specific to our study, fear of crime related to police actions and efforts after victimization. The current study fills the gap by determining whether there is, indeed, a relationship between police effort and violent crime victims’ fear. Results show a positive relationship between police effort subsequent to victimization and violent crime victims’ fear. Discussion of the results and limitations of the study are included.